Bringing Lead Awareness into the Classroom: A Multigrade Curriculum Connecting Environmental Chemistry and Public Health - Eshaan M. Patel; Rylie P. Boezeman; Khaled M. Masharqa; Noah C. Bajuyo; Kamila Deavers (Journal of Chemical Education, 2026)
Abstract Lead poisoning, a legacy of industrial pollution, remains a serious public health risk in major industrial cities. Aging infrastructure, contaminated soil, and persistent environmental inequities contribute to ongoing exposure, disproportionately affecting low-income communities and children. Recognizing the urgent need for prevention strategies, a student-led research team at Marian University developed “The Lead Poisoning Prevention Program,” an educational outreach initiative that addresses lead exposure risks through school-based learning. “The Lead Poisoning Prevention Program” is a four-session curriculum for students in Pre-K through eighth grade, incorporating hands-on activities, nutrition education, and environmental science. Instruction focuses on building knowledge and practical prevention strategies, including the TCTT method (Test soil, Cover the soil, Take off shoes, Test child). Other topics include sources of lead, the role of diet in reducing lead absorption, and sustainable remediation using phytoremediation techniques. To extend impact beyond the classroom, the program incorporates interactive activities, bilingual brochures, and take-home soil sampling kits that promote family engagement and community action. Across schools in Indianapolis, the program has consistently demonstrated student engagement, gained educator support, and fostered meaningful family participation. Soil analyses collected during implementation indicate that nearly 23% (n = 101) of student-submitted samples exceed the Environmental Protection Agency (EPA) threshold screening level. This article describes the program’s scientific background, curriculum design, pedagogy, implementation, and outcomes, highlighting the value of chemistry-based outreach for community health and STEM engagement.